Enhancing Social Networking Technologies Adoption through Perceived Usefulness: the setting of Ugandan Institutions of Higher Learning - Bwiino, Keefa; Mayoka, Kituyi Geoffrey; Musenze, Ibrahim A. (Asian Journal of Computer and Information Systems, 2016)
Social Networking Technologies (SNTs) play a major role in education by improving student academic performance through informal learning. The purpose of this study was to examine the influence of Perceived Usefulness on the adoption of Social Networking Technologies in institutions of higher learning in Uganda. A cross sectional survey methodology was employed to gather data from 146 institutions of higher learning on the variables captured by the modified Perceived Usefulness construct of the Technology Acceptance Model. Results of correlation and regression analysis indicated that a positive and significant relationship exists between Perceived Usefulness and SNTs adoption. These findings have theoretical implications for models of SNTs adoption and practical interventions designed at increasing use of SNTs. The findings of this study suggests that managers of higher institutions of learning should advice users on the usefulness of SNTs adoption in learning so as to improve on their academic job performance, increase productivity and enhance effectiveness in teaching and learning in institutions of higher learning in Uganda.
Keywords: Social Networking Technologies; Perceived Usefulness; Technology Acceptance Model; User Generated Content; SNT Adoption